The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1023/b:verc.0000012113.95479.2f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the API 20E and BBL Crystal E/NF Identification Systems for Differentiating Bacterial Isolates from Apparently Healthy Reared Sea Bass (Dicentrarchus labrax)

Abstract: The ability of two commercial rapid identification systems, API 20E and BBL Crystal E/NF, to reliably identify bacterial isolates from the internal organs of reared sea bass were compared. The tests gave different results: API 20E identified bacteria as Pseudomonas spp. with 37% accuracy, while BBL Crystal E/NF identified them as Flavobacterium odoratum with 99% accuracy. Although F. odoratum is not a marine fish pathogen, conventional tests conducted with the same isolates were more indicative of them being F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Randomly taken samples of bacteria and yeasts were characterized with API 20E and API 20 AUX strips, respectively (BioMérieux, Marcy l'Etoile, France). API 20E is one of the most commonly used kits for the rapid diagnosis of bacteria from fish (Popovic et al ., 2004). The strips were used according to the manufacturer's instructions, except for the suspension medium, which was replaced by sterile half‐salinity water for the marine isolates.…”
Section: Methodsmentioning
confidence: 99%
“…Randomly taken samples of bacteria and yeasts were characterized with API 20E and API 20 AUX strips, respectively (BioMérieux, Marcy l'Etoile, France). API 20E is one of the most commonly used kits for the rapid diagnosis of bacteria from fish (Popovic et al ., 2004). The strips were used according to the manufacturer's instructions, except for the suspension medium, which was replaced by sterile half‐salinity water for the marine isolates.…”
Section: Methodsmentioning
confidence: 99%
“…The phenotypic characterisation of the isolates was determined with API 20 E strips according to manufacturer's instructions (bioMérieux). It has been reported that API 20E is the most commonly used kit for rapid diagnosis of bacteria from fish (Popovic et al, 2004). API 20 E profiles were compared using the Wagner parsimony method, using Mix of Phylip (Felsenstein, 1996), to arrange the strains in dendrograms drawn with Fixdtree (Felsenstein, 1996) in order of similarity.…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…For the identification of sea fish isolates, Grisez et al (1991) suggested the following modifications of the prescribed method for the inoculation of the test strip: increasing of the incubation time to 48-72 hours, lowering the incubation temperature to 26°C, using a suspension of 1.5% saline as inoculum, and allowing only fermentation of sugars by sealing these cups with sterile mineral oil. In our previous study we described sea fish bacteria determination according to Grisez et al (1991) additionally lowering the incubation temperature to 22°C (Coz-Rakovac et al, 2002;Topic Popovic et al, 2004). Bertone et al (1996) used modified API 20E for sea fish bacteria, particularly a 2% NaCl modified diluent, and incubation at 25°C for 24-72 hours, according to MacDonnel et al (1982).…”
Section: Adaptation Of Api 20e For Fish Bacterial Isolatesmentioning
confidence: 99%